Sanksi Pidana Terhadap Pelanggar Protokol Kesehatan Pandemi Covid-19 - Anita Atma Negara (JURNAL HUKUM, POLITIK DAN ILMU SOSIAL, 2022)
Sanctions are an important closing part in administrative law. In a sociological context, sanctions are a form of law enforcement effort. Law enforcement is a process to make legal wishes come true. The sanctions themselves can be in the form of criminal sanctions, civil sanctions, and also administrative sanctions. The purpose of this study is to find out the prosecution of people who do not use masks according to governor regulations and to find out the criminal status of people who are subject to administrative fines including criminal acts according to the article regarding the application of discipline to health protocols in the new era of life. This research method uses normative legal research methods. The results of the study show that the application of sanctions for violations of health protocols during the Covid-19 pandemic in Indonesia is regulated in various Mayoral or Governor Regulations of each region by imposing written warning sanctions, administrative sanctions, social sanctions and criminal sanctions on violators.